Neuronal nicotinic acetylcholine receptors serve as sensitive targets that mediate bold beta-amyloid neurotoxicity - LIU Qiang; WU Jie (Acta Pharmacologica Sinica, 2016)
Alzheimer's disease (AD) is the most common form of brain dementia characterized by the accumulation of beta-amyloid peptides (Abeta) and loss of forebrain cholinergic neurons. Abeta accumulation and aggregation are thought to contribute to cholinergic neuronal degeneration, in turn causing learning and memory deficits, but the specific targets that mediate Abeta neurotoxicity remain elusive. Recently, accumulating lines of evidence have demonstrated that Abeta directly modulates the function of neuronal nicotinic acetylcholine receptors (nAChRs), which leads to the new hypothesis that neuronal nAChRs may serve as important targets that mediate Abeta neurotoxicity. In this review, we summarize current studies performed in our laboratory and in others to address the question of how Abeta modulates neuronal nAChRs, especially nAChR subunit function.